Patient Blood Management in Europe: surveys on top indications for red blood cell use and Patient Blood Management organization and activities in seven European university hospitals. Issue 4 (10th August 2016) - Bruun, M. T.; Pendry, K.; Georgsen, J.; Manzini, P.; Lorenzi, M.; Wikman, A.; Borg‐Aquilina, D.; van Pampus, E.; van Kraaij, M.; Fischer, D.; Meybohm, P.; Zacharowski, K.; et al.
Abstract : Background and Objectives: Patient Blood Management ( PBM ) in Europe is a working group of the European Blood Alliance with the initial objective to identify the starting position of the participating hospitals regarding PBM for benchmarking purposes, and to derive good practices in PBM from the experience and expertise in the participating teams with the further aim of implementing and strengthening these practices in the participating hospitals. Methods: We conducted two surveys in seven university hospitals in Europe: Survey on top indications for red blood cell use regarding usage of red blood cells during 1 week and Survey on PBM organization and activities . Results: A total of 3320 units of red blood cells were transfused in 1 week at the seven hospitals. Overall, 61% of red cell units were transfused to medical patients and 36% to surgical patients, although there was much variation between hospitals. The organization and activities of PBM in the seven hospitals were variable, but there was a common focus on optimizing the treatment of bleeding patients, monitoring the use of blood components and treatment of preoperative anaemia. Conclusion: Although the seven hospitals provide a similar range of clinical services, there was variation in transfusion rates between them. Further, there was variable implementation of PBM activities and monitoring of transfusion practice. These findings provide a baseline to develop joint action plans to further implement and strengthen PBM across a number of hospitals in Europe.